(untitled) (Research, Society and Development, 2021)
The objective of this research is to discution how synonyms and the expansion of the occurrence area in Brazil of Attalea phalerata, in the region of Amazon River, State of Amapá. The material was collected in the municipality of Mazagão, an experimental area of EMBRAPA, Amapá. The description and morphometry were carried out at Amapaense Herbarium (HAMAB), of the Instituto de Pesquisas Científicas e Tecnológicas do Estado do Amapá (IEPA). The board was composed using Adobe Photoshop software and the morphometric analysis was performed in vivo. The results indicate several synonyms attributed to the species, as a result of the rearrangement in the definition of the species of the genus Attalea. The results of this study enable knowledge of Brazilian flora to expand the geographical distribution of A. phalerata to the State of Amapá. It is concluded that the importance of plant taxonomy is justified, among several aspects, in order to clarify and support the use of specific and generic denominations accepted, based on the current Classification System, but also, it reinforces the importance of Classical Taxonomy for the Modern Science.